Implementasi Putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010 tentang Anak di Luar Nikah (Studi Kasus di Kabupaten Kuningan) - Deby Deviyanti; Haris Budiman; Bias Lintang Dialog (Universitas Kuningan, 2018)
AbstractThe author conducted this research with the background of how the status of children out of wedlock according to the Law of 1974 on Marriage. The purpose of writing this thesis to know an examine how the status outside of marriage according to Law Number 1 Year 1974 about Marriage and to know how the legal effect on the status of children outside marriage after the decision of the Constitutional Court Number 46/PUU-VIII/2010. The method used in this research is with the normative juridical approach, in normative law research, then investigated initially secondary data. The result of this study is the regulation of marital status of children outside of marriage regulated in Article 43 paragraph (1) of Law Number 1974 about concerning marriage. The conclusion of the writing of this thesi is the Chief Justice Mahfud MD declared that children born outside the relationship of marriage or uitside the official relationship still have a relationship with his father. In the Constitutional Court’s declaration, the child who is married outside the marriage has a civil relationship with his mother and his mhoter’s family and with his father as p[roved by science and technology and or other evidence according to the law has blood relation, including civil relationships with his father’s family.Keyword: Marriage, Child Status AbstrakPenulis melakukan penelitian ini dengan latar belakang yaitu bagaimana status anak di luar nikah menurut Undang-Undang Tahun 1974 tentang Perkawinan. Tujuan penulisan skripsi ini untuk mengetahui dan mengkaji bagaimana status diluar nikah menurut Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan dan untuk mengetahui bagaimana akibat hukum terhadap status anak diluar nikah setelah putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010. Metode yang digunakan dalam penelitian ini adalah dengan pendekatan yuridis normatif, dalam penelitian hukum normatif maka yang diteliti pada awalnya data sekunder, lokasi penelitian di kabupaten kuningan. Hasil penelitian ini adalah pengaturan status anak diluar nikah diatur dalam Pasal 43 ayat (1) Undang-Undang Nomor 1974 tentang perkawinan. Kesimpulan dari penulisan skripsi ini adalah Ketua Majelis Hakim Mahfud MD menyatakan bahwa anak lahir diluar hubungan pernikahan atau diluar hubungan resmi tetap memiliki hubungan dengan ayahnya. Dalam Putusan MK disebutkan anak yang dilahitkan diluar perkawinan mempunyai hubungan perdata dengan ibunya dan keluarga ibunya serta dengan laki-laki sebagai ayahnya yang dapat dibuktikan berdasarkan ilmu pengetahuan dan teknologi dan atau alat bukti lain menurut hukum mempunyai hubungan darah, termasuk hubungan perdata dengan keluarga ayahnya.Kata kunci : Perkawinan, Status Anak